AKR2A is involved in the flowering process of Arabidopsis thaliana. (31st December 2022) - Tang, Qian; Zhao, Ya-Nan; Luo, Shan; Lu, Shan
ABSTRACT: Flowering at an appropriate time is crucial for plant development and reproduction. In Arabidopsis, the flowering process is managed by a regulatory network composed of at least 6 independent pathways. As a core protein in flowering regulation, FLOWERING LOCUS T (FT) participates in almost all these pathways. ANKYRIN REPEAT-CONTAINING PROTEIN 2A (AKR2A) was initially discovered as a 14-3-3-interacting protein. It was then found to be involved in the transportation of chloroplast outer membrane proteins and the resistance to low-temperature stress. Here, we identified an akr2a null mutant with a delayed flowering phenotype. Through the quantitative real-time PCR (qRT-PCR) and bimolecular fluorescence complementation (BiFC) assays, we demonstrated that AKR2A modulates the flowering process through its interaction with FT.